Population fluctuation of Anastrepha Schiner (Diptera: Tephritidae) species in Manaus Region, AM, Brazil - Ronchi-Teles, Beatriz; Silva, Neliton Marques da (Neotropical Entomology, 2005)
The population fluctuation of Anastrepha Schiner (Diptera: Tephritidae) species captured in McPhail traps was examined. Specimens of Anastrepha were collected weekly over a period of 80 weeks, from May 1996 to December 1997. The traps were baited with sugarcane syrup (10%) and distributed in two localities along the BR 174 highway: km 23 and km 40, north of Manaus, AM, Brazil. Thirteen species were collected: A. striata Schiner, A. obliqua (Macquart), A. leptozona Hendel, A. serpentina (Wied), A. distincta Greene, A. bahiensis Lima, A. antunesi Lima, A. coronilli Carejo e Gonzalez, A. furcata Lima, A. atrigona Hendel, A. flavipennis Greene, A. zernyi Lima and Anastrepha sp. 2 (not identified). The decisive factor governing the occurrence and population fluctuation of fruit flies was found to be the presence of fruit hosts rather than the abiotic factors. There was low correlation (r = 0.074, P > 0.05) between the number of fly/trap/day (FTD) and the precipitation. The time of highest precipitation coincided with the peak period of fructification. Unmeasured factors, such as alternative hosts, natural enemies and host succession probably influence the population of flies. For our knowledge, this is the first record of A. zernyi in Northern of Brazil.
Flutuação populacional de espécies de Anastrepha Schiner (Diptera: Tephritidae) na Região de Manaus, AM
Keywords: Anastrepha; Anastrepha Bahiensis; Anastrepha Coronilli; Anastrepha Distincta; Anastrepha Flavipennis; Anastrepha Leptozona; Anastrepha Obliqua; Anastrepha Serpentina; Anastrepha Striata; Diptera; Insecta; Tephritidae